The 2008 Olympic Games: Leveraging a "Best Ever" Games to Benefit Beijing - Tian, Jing (Auckland University of Technology, 2006)
This Thesis undertakes a leverage analysis of mega-events in the context of the 2008 Beijing Olympic Games. A leverage analysis apparently different from a impact analysis; it focuses on how to maximize the potential positive impacts and minimize the negative impacts for an event that will be held in the future. To analyze the circumstance of the Beijing Olympics that are amendable to leveraging, the research methodology employed is empirical with method of semi-structured in-depth interviews with the government officials, tourism industry people and the local community members in Beijing. This thesis research conducted a leveraging analysis from three perspectives: environmental, socio-cultural, and tourism/economic perspectives. From each perspective, four angles would be investigated: identifying the potential impacts of 2008 Olympics; determining the leveraging activities for the potential impacts; uncovering the opportunities for leveraging the potential impacts, and exploring the challenges in leveraging the potential impacts. Because there is not any existing theory on a leverage analysis in the context of Beijing Olympic Games, this research was conducted with the guidance of “grounded theory”. The research indicated that the government aims to take use of the opportunity of hosting the “Green Olympics” to reap the ambition of making Beijing into a “greener” city, but how long would the policies last when the games are over is essential for the effectiveness. Similarly, the socio-culture would be leveraged by implementing the “People’s Olympic” theme. Finally, the tourism in Beijing would be leveraged by a series of leveraging activities derived form the Olympic Games. The findings of this thesis research will contribute to the event studies and the leveraging studies.
Keywords: Olympic Games (29th : 2008 : Beijing, China) -- Economic aspects